280 Descriptive Characteristics of Preweaned Heifer Raising Practices on China Dairy Farms: Colostrum Quality, Passive Transfer Status and Growth Performance. (8th October 2021) - Liu, Shuai; Chen, Tianyu; Li, Jiaqi; Guo, Wenli; Peng, Rong; Cao, Zhijun
Abstract: Few data are available on the descriptive characteristics of colostrum quality, passive transfer status and growth performance within a national population in China. This study included 110 dairy operations in 23 provinces, and data were obtained from management software, report system and questionnaires from 2015 to 2019. Data were analyzed using SAS (version 9.0, SAS Institute Inc., Cary, NC, USA). The results showed that colostrum quality was measured in 96.4% of farms and colostrum was pasteurized in 91.8% of farms. 83.6% of colostrum was excellent (Brix > 22%). Colostrum could be fed to calves within 1 hour after birth in 86.4% of farms. Besides, calves that experienced failure of passive transfer (serum total protein < 5.2 g/dl) decreased from 2015 to 2019 and accounted for 0.75% of calves in 2019. Most farms (48.8%) feed 400 kg - 600 kg milk during the preweaning period and whole milk was the main type of liquid diet accounting for 70.6% of farms. Meanwhile, 22.0% of farms chose to feed forage before weaning, and 90.1% of these farms fed oat hay. The average birth weight of calves was 37.8 kg and the average daily gain of preweaning calves was 848.3 g/d. For preweaning calves, the proportion of single housing was more than 60%, whereas postweaning calves were mainly raised in groups. The morbidity of preweaning calves in China decreased annually, from 43.3% in 2015 to 25.4% in 2019. Digestive diseases and respiratory diseases were two main diseases, and accounted for 46.0% and 38.4%, respectively. This study provides an overview on dairy calves raising practices in China.